2006
DOI: 10.1002/ejic.200500634
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Redox Chemistry of Ruthenium Metallopharmaceuticals: The Electrochemical Behaviour of [LH][trans‐RuIIICl4L2] (L = imidazole or indazole) Complexes

Abstract: Here we report the findings from a study on the electrochemical behaviour of two Ru III complexes [LH][trans-Ru III Cl 4 L 2 ] (L = imidazole, ICR, or indazole, IndCR) in aqueous solution at different pH values. An electrochemically reversible and chemically quasi-reversible one-electron reduction is observed for both compounds. Despite the similarity of the structures, the fate of the electrogenerated Ru II species is different; in the case of ICR, imidazole, followed by a chloride

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…Osella and co-workers reported that ICR (as sodium salt) is reduced in vitro within min-utes by a two-fold excess of glutathione at 37.0 °C in a pH range from 4.0 to 7.4. [19] In contrast, Keppler and co-workers [20] established that ICR is reduced by an excess of gluthatione or ascorbic acid only at pH 7.4 but not, contrary to a previous report, [21] in pure water. Conversely, the redox potential of the indazole derivative KP1019 was found to be remarkably higher than that of ICR, ca.…”
Section: Chemical Behavior and Activation Of Nami-amentioning
confidence: 82%
“…Osella and co-workers reported that ICR (as sodium salt) is reduced in vitro within min-utes by a two-fold excess of glutathione at 37.0 °C in a pH range from 4.0 to 7.4. [19] In contrast, Keppler and co-workers [20] established that ICR is reduced by an excess of gluthatione or ascorbic acid only at pH 7.4 but not, contrary to a previous report, [21] in pure water. Conversely, the redox potential of the indazole derivative KP1019 was found to be remarkably higher than that of ICR, ca.…”
Section: Chemical Behavior and Activation Of Nami-amentioning
confidence: 82%
“…22,23 For the KP1019 complex, it is also observed an increase in the reduction potential after the first hydrolysis. Ravera et al 25 measured the reduction potential of [Ru III (H 2 O)Cl 3 (Ind) 2 ] at -0.072 V vs. Ag/AgCl, which corresponds to an increase of 0.088 V compared with the KP1019 reduction potential. Therefore, the trend observed in our computed values for NAMI-A and its hydrolysis products are in line with the experimental findings and shows that it is easier to reduce the hydrolyzed products than the original compound.…”
Section: Resultsmentioning
confidence: 99%
“…Electrochemical and chemical reduction studies of Ru III metallodrugs are, therefore, of great importance in order to understand their biological activities and thus have been the subject of several studies. [18][19][20][21][22][23][24][25][26][27] Ravera et al 25 investigated the redox chemistry of [LH][trans-Ru III Cl 4 L 2 ] (L = imidazole or indazole) complexes in water at different pH values. For the indazole and imidazole complexes the E 0 ' (Ru III /Ru II ) reduction potential of -0.160 and -0.460 V vs. Ag/AgCl was obtained at pH 4.0.…”
Section: Introductionmentioning
confidence: 99%
“…7 In contrast, ICR would need stronger reductants, which may be more rare in a biological environment. 3,21,25 Consistently, ICR has proved to be more inert than NAMI-A, and its hydrolysis path is less affected by reductants. 26 Recently, Chen et al have reported a theoretical investigation on NAMI-A and ICR hydrolyses, 27,28 focusing on Cldissociation.…”
Section: Introductionmentioning
confidence: 88%
“…6,7 Furthermore, the hydrolysis of the reduced compounds has not been considered, even though it may be important for both drugs because of the high reducing power of solid tumor tissues. 21,29 In order to understand the mechanism of action of NAMI-A and ICR at the molecular level, an extensive investigation of the hydrolysis paths in both Ru oxidation states, along with an evaluation of the reduction potentials of the two drugs and their metabolites, is needed. In this work we tackle this issue and report a systematic study of the hydrolyses of the two drugs up to the third aquation, combining density functional theory (DFT) calculations and an implicit description of the solvent through the conductor-like polarizable continuum model (CPCM).…”
Section: Introductionmentioning
confidence: 99%